A Study of Culinary Brand Identity in Banyuwangi District with the Gastronomic Tourism Concept - Ayu Wanda Febrian (Universitas Airlangga, 2019)
Banyuwangi is a city with varieties of culture. One of its well-known culture is relating to culinary diversity. Nowadays, it is undeniable that tourism in this city develops very quickly. To improve the development of tourism, the people of Banyuwangi need to focus on the concept of gastronomic tourism in creating a brand identity in order to increase the tourist buying intention. This research is a qualitative descriptive study with a case study approach. The result of this study showed that Pecel Pitik was selected as Banyuwangi gastronomic tourism brand identity. This was supported by (a) if combined with previous assessments, we found that Pecel Pitik got 84%, while Ayam Kesrut was only 37%, (b) Pecel Pitik Menu was the best-selling menu, ordered by many consumers, (c) The Philosophy of the origin of Pecel Pitik was more complete and had historical value compared to the Ayam Kesrut.